Ta'allum al Sarf al Arabī bi Istikhdām Taqniyah al Wāqiq al Mu'azzaz = Teaching and learning Arabic morphology using augmented reality technology - Md Noor, Mohamad Lukman Al Hakim; Md Ghalib, Mohd Feham (IIUM Press, 2025)
This study addresses the issue of learning Arabic verb patterns using Augmented Reality technology as it seeks to help students in learning it through the design of a programmed instructional module. The objectives are to know the learning difficulties experienced by learners majoring in Arabic language, to identify student’s preference on multimedia elements in the augmented reality technology, to design the instructional module using the augmented reality technology and to know its effectiveness on student’s performance, between male and female, and high CGPA and low CGPA. This study followed five methodological stages; descriptive, analytical, design, development and semi-experimental. The researcher collected information about the difficulties in learning Arabic verb patterns and theories of augmented reality technology for educational purposes. In addition, there were five stages of academic procedures in the light of the analysis, design, development, implementation, and evaluation (ADDIE) of instructional development model (ID). Firstly, learner’s needs analysis that was completed before the design and after that design phase of the module, then expert review which was conducted during the development phase. The data was collected using tests and questionnaires to know any significant value differences between the two comparing groups; low CGPA and high CGPA students, and between male and female students in the intervention session. The questionnaires also used to expose their opinion on learning Arabic verb patterns using Augmented Reality technology. Based on the results of the needs analysis, the researcher identified difficult topics and the student’s preferences in the elements of augmented reality technology. The researcher then designed the module using augmented reality technology in learning Arabic verb patterns. It was implemented to a sample of 70 students majoring in Arabic language at the Centre for Foundation Studies, International Islamic University Malaysia. The results confirmed that there were significant value differences for the fourth question in the test between low CGPA and high CGPA students after using the application. However, there were no significant value differences in the overall marks of the test between the two comparing groups; low CGPA and high CGPA students, and between male and female students. Moreover, this study found that learning Arabic verb patterns through Augmented Reality technology has contributed positively to their study and the researcher urge that this model to be used and implemented in different areas of teaching and learning Arabic as a second language.